Reproducibility and replicability of rodent phenotyping in preclinical studies. (April 2018) - Kafkafi, Neri; Agassi, Joseph; Chesler, Elissa J.; Crabbe, John C.; Crusio, Wim E.; Eilam, David; Gerlai, Robert; Golani, Ilan; Gomez-Marin, Alex; Heller, Ruth; Iraqi, Fuad; Jaljuli, Iman; et al.
Highlights: Many published scientific discoveries fail to replicate. The field of mouse behavioral phenotyping was one of the first to raise this concern. Replicability should be addressed at the statistical and methodological levels. The issue does not question the validity of model organisms as a whole. Community efforts and data sharing help in promoting effective solutions. Abstract: The scientific community is increasingly concerned with the proportion of published "discoveries" that are not replicated in subsequent studies. The field of rodent behavioral phenotyping was one of the first to raise this concern, and to relate it to other methodological issues: the complex interaction between genotype and environment; the definitions of behavioral constructs; and the use of laboratory mice and rats as model species for investigating human health and disease mechanisms. In January 2015, researchers from various disciplines gathered at Tel Aviv University to discuss these issues. The general consensus was that the issue is prevalent and of concern, and should be addressed at the statistical, methodological and policy levels, but is not so severe as to call into question the validity and the usefulness of model organisms as a whole. Well-organized community efforts, coupled with improved data and metadata sharing, have a key role in identifying specific problems and promoting effective solutions. Replicability is closely related to validity, may affect generalizability and translation of findings, and has important ethical implications.